Implicações do cuidar de crianças com necessidades especiais de saúde: possibilidades para o cudado familial e de enfermagem - Pieszak, Greice Machado (2013)
Qualitative research, exploratory, descriptive study aimed to understand the implications of caring for a Child with Special Needs Health for the family. Data were collected with ten families, between January and February 2012, through triangulation techniques, collecting records, semi-structured interview and the construction of the genogram and eco-map. The analysis followed the principles of thematic content analysis. The results showed that disclosure of the diagnosis has implications for the family, especially when it comes to late diagnosis. For social networks and specific restricted, the difficulties faced by the families of these children access to health services and education. These difficulties highlighted reverberate in the daily care of children with health needs and in time, give way to routine and adapting to everyday life for their families, triggering changes in restructuring involving familial. We conclude that the reorganization of families happens from the disease condition of the child established. The difficulties faced by these families are related to the completeness and accessibility of health services and actions and can generate repercussions on living conditions of children and their families and the need for reconfigurations for family care. It is recommended the recognition and appreciation of the family as the unit of care, promotion and coordination of support networks for family reorganization and actions centered on the health of the child and his family.